Clinical outcome endpoints in heart failure trials: a European Society of Cardiology Heart Failure Association consensus document. (October 2013) - Zannad, Faiez; Garcia, Angeles Alonso; Anker, Stefan D.; Armstrong, Paul W.; Calvo, Gonzalo; Cleland, John G.F.; Cohn, Jay N.; Dickstein, Kenneth; Domanski, Michael J.; Ekman, Inger; Filippatos, Gerasimos S.; Gheorghiade, Mihai; et al.
<x xml:space="preserve">Abstract</x> Endpoint selection is a critically important step in clinical trial design. It poses major challenges for investigators, regulators, and study sponsors, and it also has important clinical and practical implications for physicians and patients. Clinical outcomes of interest in heart failure trials include all‐cause mortality, cause‐specific mortality, relevant non‐fatal morbidity (e.g. all‐cause and cause‐specific hospitalization), composites capturing both morbidity and mortality, safety, symptoms, functional capacity, and patient‐reported outcomes. Each of these endpoints has strengths and weaknesses that create controversies regarding which is most appropriate in terms of clinical importance, sensitivity, reliability, and consistency. Not surprisingly, a lack of consensus exists within the scientific community regarding the optimal endpoint(s) for both acute and chronic heart failure trials. In an effort to address these issues, the Heart Failure Association of the European Society of Cardiology (HFA‐ESC) convened a group of expert heart failure clinical investigators, biostatisticians, regulators, and pharmaceutical industry scientists (Nice, France, 12–13 February 2012) to evaluate the challenges of defining heart failure endpoints in clinical trials and to develop a consensus framework. This report summarizes the group's recommendations for achieving common views on heart failure endpoints in clinical trials.